A contact-based technique for measurement of membrane tension. (1st November 2022) - Aminian, Behzad; Abadi, Iman Rahgozar; Green, Sheldon; Rogak, Steven
Abstract: Membranes are used widely in engineering applications, including the porous membranes in fuel cells and ventilation systems. In order to understand the mechanical behavior of the membrane, one should know the loads acting on it, including the tension applied to it during the manufacturing process. This study describes a novel contact-based method to measure the pre-tension for applications, such as membrane energy exchangers, where optical access to the membrane is limited. The method involves direct measurement of the membrane location under various pressures, using a novel probe, and inferring the pre-tension by comparing the results with theoretical models. The technique is validated by measuring the tension of membranes pre-tensioned to known values. The RMS deviation between the measured tension and the set pre-tension is 0.55 N m −1, which is approximately 3% of the pre-tension used in a typical membrane energy exchanger.